From sleeplessness to solitude: emotional repair as a buffer between insomnia and loneliness in university students - Ostrow, Katherine Domar; Rieur, Olivia; Moeller, Robert W.; Seehuus, Martin (Frontiers in Sleep, 2025)
Loneliness and insomnia are endemic in college students, and emotion regulation is strongly related to both. Starting with a biopsychosocial framework, the present study tested a model in which emotional repair mediated the relationship between loneliness and insomnia, with the goal of using a potential mechanism of action to address loneliness. Participants were undergraduate students (N=1,513) in the United States who completed a survey including the Trait Meta-Mood Scale, Sleep Condition Indicator, and UCLA Loneliness Scale, amongst other measures. Insomnia had a significant total negative effect on loneliness, B = −0.46, 95% CI [−0.54, −0.39]. Emotional repair partially mediated this relationship, with an indirect effect of B = 0.015, 95% CI [−0.19, −0.12]. Participants with better sleep were more able to regulate their emotions, and thus tended to experience lower levels of loneliness. Treating insomnia (e.g., CBT–I) or skills associated with emotional repair and regulation (e.g., transdiagnostic approaches to emotion regulation) could reduce overall loneliness.